2016
DOI: 10.1109/tpwrd.2015.2403278
|View full text |Cite
|
Sign up to set email alerts
|

New Metric Recommended for IEEE Standard 1547 to Limit Harmonics Injected Into Distorted Grids

Abstract: IEEE Std. 1547 defines grid connection standards for distributed resources (DR). This standard sets requirements for harmonic performance, which are particularly relevant when converter interfaced DRs are considered. Specifically, the standard limits the allowable harmonic current injected by a DR, assuming grid voltage at the point of common coupling (PCC) is harmonic free. In this paper it is demonstrated, both mathematically and experimentally, that the harmonic current injection of a converter interfaced D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…With the development of smart grids, increasing numbers of power electronic devices have been connected to distribution networks, which inject a large amount of harmonics [1][2][3][4][5]. Various electrical power equipment and electronic products have a strong sensitivity to the harmonics in the distribution network, making harmonic elimination of great importance [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of smart grids, increasing numbers of power electronic devices have been connected to distribution networks, which inject a large amount of harmonics [1][2][3][4][5]. Various electrical power equipment and electronic products have a strong sensitivity to the harmonics in the distribution network, making harmonic elimination of great importance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Such detailed information is not typically available to customers. It has been recently shown that the FCM of a power converter can alternatively be obtained with a high degree of accuracy from simple experimental measurements at the terminals of the converter, with the converter considered as a "black box" [20], [21]. This paper builds on the experimentally identified FCM model of a converter to systematically solve for harmonic interactions between the grid and the converter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a measurement-based approach was examined for directly determining the FCM via experiments [20], [21]. This approach requires no knowledge of the converter topology, parameter values, nor controller details.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, reference [8] deals with the power transfer capability problem of DGUs including harmonic distortion, and considering power quality regulations at a speci c point of the network. Reference [9] brings out some pitfalls of electric power quality indexes allowed by international regulations showing that being within the limits is not enough in order to ensure proper performance of the DGUs electrically close to each other. In more sophisticated approaches, the power quality on the distribution system is improved by the use of harmonic compensation methods in the control schemes of the interconnected DGUs [10]- [14].…”
mentioning
confidence: 99%